2018
DOI: 10.1111/jfd.12828
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immune responses and effectiveness of refined outer membrane protein vaccines against Vibrio harveyi in orange‐spotted grouper (Epinephelus coioides)

Abstract: Vibriosis is a severe infection occurring in many commercially important marine fish species. In this study, vaccines containing Vibrio harveyi recombinant outer membrane protein K (rOmpK), outer membrane protein U (rOmpU) and rOmpK-OmpU fusion protein in addition to the metabolizable Montanide ISA 763 A VG adjuvant were developed and evaluated in the orange-spotted grouper. The results indicate that recombinant V. harveyi protein-based vaccines resulted in a remarkably higher expression of IL-1β and IL-8 at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…injection (dose = 100 µl/fish) estuary cod (Epinephelus coioides) leading to an RPS or 60% or 70% depending on the challenge culture. A recombinant fusion protein r-OmpK-OmpU controlled disease in orange-spotted grouper (RPS = 81.8%) (Nguyen et al 2018). Subsequently, the OMP To1C, which is a major adhesin, was used successfully to protect hybrid grouper (E. fuscoguttatus × E. lanceolatus) against experimental challenge (Zhu et al 2019).…”
Section: Vaccinesmentioning
confidence: 99%
“…injection (dose = 100 µl/fish) estuary cod (Epinephelus coioides) leading to an RPS or 60% or 70% depending on the challenge culture. A recombinant fusion protein r-OmpK-OmpU controlled disease in orange-spotted grouper (RPS = 81.8%) (Nguyen et al 2018). Subsequently, the OMP To1C, which is a major adhesin, was used successfully to protect hybrid grouper (E. fuscoguttatus × E. lanceolatus) against experimental challenge (Zhu et al 2019).…”
Section: Vaccinesmentioning
confidence: 99%
“…Although other antigens have been pointed out as vaccine candidates, like TolC, an outer membrane protein from V. harveyi ( 85 ) and DNAj ( 86 ), several experimental vaccines using OmpK were described as efficient. For instance, vaccination of Orange-spotted groupers with a recombinant OmpK induced a higher tolerance to Vibrio infections ( 83 ); a subunit vaccine involving OmpK and OmpU fusion resulted in a protective effect against V. harveyi infection and showed potential against other species ( 87 ); E. coli based recombinant vaccines containing OmpK were efficient against challenge with multiple strains of V. harveyi , V. alginolyticus , and V. parahaemolyticus ( 86 ). Nonetheless, studies regarding either the immunogenicity of OmpK or the cross-protection effect of recombinant OmpK vaccines are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The high immunogenicity of outer membrane proteins (OMP) is considered a promising candidate for the design of antimicrobial drugs and vaccines in various pathogenic strains. Numerous other studies have reported that outer membrane proteins (OMPs) are generally very immunogenic due to their exposed epitopes on the cell surface ( 176 ) and have the potential of a vaccine candidate for fish against V. anguillarum ( 177 , 178 ), Vibrio mimicus ( 179 ), V. harveyi ( 180 ), Vibrio ichthyoenteri ( 181 ), P. olivaceus ( 182 ), E. tarda ( 183 ) and A. hydrophila ( 184 ) infection. Flagellin is also well-studied and effective subunit vaccine candidate ( 185 ).…”
Section: Classification and Preparation Technology Of Aquatic Vaccinesmentioning
confidence: 99%